Empirical modeling, simulation and control of spray drying process using nozzle atomizer spray dryer - Tan, Lee Woun (2011)
Spray drying is a convenient dehydration technique in producing food powders. The characteristics of product depend on the drying parameters and characteristics of the liquid feed. Controlling the spray dryer is vital to ensure that the product meets the quality specifications, even when disturbance occurs. In order to control the spray dryer, the development of dynamic model is required. The main objective of this study is to investigate the dynamic behavior of the spray drying process and suggest the suitable control strategy using proportional-integral (PI) controller. Before developing the dynamic model, a preliminary study was conducted and the outlet air temperature was identified as the controlled variable and inlet air temperature as the manipulated variable. Dynamic models that gave the best prediction of the dynamic response of nozzle atomizer spray dryer for orange juice powder (with maltodextrin) and whole milk powder (without maltodextrin) were developed empirically. In addition, the models that show the effect of selected disturbance on the dynamic response of spray dryer was also developed. All models were represented as first order plus time delay (FOPTD) and valid because R2>0.6. Furthermore, the control of the spray dryer in this study engages a PI controller for the set point change and disturbance change. High overshoot is a problem in many processes, thus a lambda, λ guideline for direct synthesis tuning method was proposed to enable users to define the specified overshoot, and its performance and robustness were found to be satisfactory. When this method was applied in this process, it provided good performance in the set point change, more robust and less sensitive to the error but demonstrated slow performance (2-5 minutes) in disturbance change.